Evaluating the concentrations of total mercury, methylmercury, selenium, and selenium:mercury molar ratios in traditional foods of the Bigstone Cree in Alberta, Canada. (July 2020) - Golzadeh, Nasrin; Barst, Benjamin D.; Basu, Niladri; Baker, Janelle M.; Auger, Josie C.; McKinney, Melissa A.
Abstract: Traditional foods provide nutritional, social, and economic benefits for Indigenous communities; however, anthropogenic activities have raised concerns about mercury (Hg), especially methylmercury (MeHg), in these foods. This issue may be of particular concern for communities near large industrial activities, including the Bigstone Cree Nation adjacent to the Athabasca oil sands region, Canada. This community-led study sought to assess variation in THg and MeHg concentrations among traditional food types (plants or animals), species, and tissues (muscles, organs), and variation in concentrations of the micronutrient selenium (Se)— thought to protect against Hg toxicity—and Se:THg ratios. Thirteen plant and animal species were collected in 2015 by Bigstone Cree community members. We quantified THg, Se, and Se:THg ratios in 65 plant and 111 animal samples and MeHg in 106 animal samples. For plants, the lichen, old man's beard ( Usnea spp.), showed the highest concentrations of THg and Se (0.11 ± 0.02 and 0.08 ± 0.01 μg g −1 w. w., respectively) and also had a low Se:THg molar ratio. Concentrations of THg, MeHg, and Se differed among animal samples ( P  < 0.010), showing variation among species and among tissues/organs. Generally, concentrations of THg and MeHg were highest in aquatic animals, which also had relatively low Se:THg molar ratios. Overall results revealed substantial variation in the patterns of THg, MeHg, Se and Se:THg ratios across this comprehensive basket of traditional foods. Thus, measuring concentrations of THg alone, without considering MeHg and potential associations with Se, may not adequately convey the exposure to Hg in traditional foods. Highlights: Hg and Se were measured in traditional foods in the Athabasca region, Canada. Total Hg (THg) and Se were detected in all plant and animal samples. Methylmercury (MeHg) was measured and detected in most animal tissues and organs. THg, and also Se:Hg molar ratios, were generally higher in animals than in plants. THg and MeHg were higher in aquatic animals than in terrestrial animals.